Strategi Komunikasi Wisatawan Gundaling dalam Meningkatkan Minat Berkunjung di Berastagi - Sembiring, Sarah Isari Br.; Riadi, Selamat (Mahesa Research Center, 2025)
This study aims to analyze the communication strategies used by tourists to increase interest in visiting the Gundaling tourist destination in Berastagi. This research stems from the phenomenon of tourists’ growing role as communication agents in promoting destinations through various communication channels, both interpersonal and digital. The research employs a qualitative approach with data collection techniques including in-depth interviews, direct observation, and social media content analysis. The findings indicate that tourists utilize four main communication strategies: interpersonal communication through direct recommendations, digital communication via social media, digital content creation, and testimonials on review platforms. These strategies effectively build a positive image of the destination, attract potential visitors, and increase the number of visits. This study confirms that tourists play a significant role in the organic promotion of tourist destinations, and their involvement in communication strategies can be a more authentic approach compared to formal marketing campaigns. Therefore, destination managers and governments need to support and optimize the role of tourists in tourism communication strategies.